Diverse Positions, Shared Ethics: A Review of Soundwalking: Through Time, Space, and Technologies - Jacek Smolicki (ed.). Abingdon: Routledge (The Focal Press), 2023 - Dantas, Paulo (2023)
Throughout this review, I will explore the impact of Smolicki’s questions through some of the texts contained in this book, with the support of a handful of its important references – mainly Dylan Robinson (2020), Val Plumwood (1995) and Sara Ahmed (2006). Before proceeding, I need to take a closer look at the aforementioned questions in order to establish my orientation marks, the themes that will loosely anchor this review. First, I am interested in understanding how soundwalking can be deployed as a technique or a condition “for disrupting the familiar.” That initial investigation will then allow me to consider the aims towards which this technique could be deployed, i.e., “familiarizing with the unknown” and “reconfiguring how we sense and act in the world today.” If the hypothesis implied in Smolicki’s questions holds, namely, if soundwalking can, in fact, be considered as a method to help us actualize the recurring metaphor of listening as an “openness to the exterior world to take input and be disturbed” (Droumeva, p. 80), and if said disturbances can indeed reconfigure how we sense and act in the world, then soundwalking might be considered a tool in service of a wider ethical program, one that facilitates a better attunement “to the particular filters of race, class, gender, and ability that actively select and frame the moment of contact between the listening body and the listened-to sound” and a “listening otherwise” (Robinson, p. 11) oriented towards social and environmental justice.
FRIS
1
Keywords: Music, Thought and Technology